Pengaruh Sumber Informasi Terhadap Keputusan Masuk Universitas Muhammadiyah Palembang - Diah Isnaini Asiati (Universitas Muhammadiyah Ponorogo, 2017)
This research is developed using an associative design with connecting the variables of personal resource, commercial resource, public resource, and experience resource, to the decision of chosing UMP. There are five variables which are developed into several indicators. The number of sample is determined by a formula or Isaac Michael with the fault rate at 5%. There are 207 students who taked by proportional cluster sampling. The required data is the primary data in the form of respondent answers. Then the data analysis method is multiple linear regression. The obtained results are the R value of 0.723 which means that there is a strong relationship positively and significantly between personal resource, commercial resource, public resource, and experience resource, to the student decision